The Influence of Broccoli Extract (Brassica oleracea var. Italica) to Liver Cells Damage in Mice (Mus musculus) Induced by Paracetamol - Shinta Retno Wulandari; Endang Listyaningsih Suparyanti; Ratih Puspita Febrinasari (Nexus Biomedika, 2016)
Introduction : Broccoli is known to contain antioxidants such as vitaminC, flavonoids and sulforaphane. Antioxidants can protect liver from damage caused by free radicals. This study aims to prove that broccoli extract protect liver cell from damage in mice induced by paracetamol in toxic dose and an increased doses of broccoli extract enhance the effects of protection to liver cell in mice. Methods : This study was an experimental laboratory with post test only controlled group design. Samples (30 mice) were taken by incidental sampling. Samples divided randomly into 5 groups, each group consisted of 6 mice. K1 was given distilled water. K2 was given paracetamol in toxic dose. KP1, KP2 and KP3 were given broccoli extract dose I, II and dose III respectively for 14 days and also were given paracetamol in toxic dose on day 12, 13 and 14. On day 15, the livers of mice were taken for making preparations with HE staining. The liver cell damages were observed by counting the nuclei of cells undergoing pyknosis, karyorrhexis and karyolysis. Data were analyzed by Oneway ANOVA and Post Hoc LSD analysis test (? = 0.05). Result : K2 had the most damaged cells (157.17 7.834 cells) and the least damaged cells were at K1 (1.50 1.049 cells). Oneway ANOVA test result was p = 0.00 (p < 0.05). Result of Post Hoc LSD analysis test showed a significant difference between groups on all pairs with p = 0.00 (p < 0.05). Conclusions : Broccoli extract protect liver cells from damage in mice induced by paracetamol. Increased doses of broccoli extract were proven to increase the protection effect on liver cells. Keywords: broccoli extract, paracetamol, liver cell damage